P667Impaired chronic hypoxic response in type 2 diabetic hearts is associated with inability to downregulate PPARa. (15th July 2014) - Mansor, L; Carr, CA; Le Page, L; Lund, T; Aasum, E; Clarke, K; Tyler, D; Heather, L
Abstract: Cardiovascular disease is the leading cause of mortality in type 2 diabetic patients. Metabolic changes and abnormal hypoxia signalling in the diabetic heart are hypothesised to decrease recovery following a myocardial infarction. Therefore the aim of this study was to investigate the cardiac metabolic adaptation to physiological hypoxia in diabetic rats. Type 2 diabetes was generated in rats using a high fat diet and low dose streptozotocin. Both control and diabetic rats were housed in hypoxia (11% oxygen) or normoxia for three weeks. Following hypoxia, control hearts had upregulated anaerobic glycolysis, increased glycogen content and suppressed fatty acid oxidation. Conversely, these hypoxia-induced metabolic changes were decreased in diabetic hearts, in that glycolysis and glycogen content remained lower, while fatty acid oxidation rates remained higher than in control hearts. Peroxisome proliferator-activated receptor α (PPARα) is a transcription factor that positively regulates fatty acid metabolism, and PPARα-regulated targets were downregulated following hypoxia in the control hearts. PPARα target proteins were upregulated in normoxic diabetic rat hearts and remained elevated following hypoxia. We found that cardiac mRNA expression of the hypoxia-inducible factor (HIF) target genes prolyl hydroxylase 3, heme oxygenase 1 and VEGF were regulated in control and diabetic hearts to the same extent, showing that there were no defects in hypoxia signalling or HIF in diabetic hearts. In conclusion, the abnormal metabolic adaptation to hypoxia in diabetes is associated with an inability of hypoxia to suppress PPARα activation, and occurs independently of changes in hypoxia and HIF signalling pathways. Thus fat metabolism is maintained to the detriment of glucose metabolism.